EZH2 deficiency attenuates Treg differentiation in rheumatoid arthritis. Issue 108 (March 2020) - Xiao, Xin-yue; Li, Yue-ting; Jiang, Xu; Ji, Xin; Lu, Xin; Yang, Bo; Wu, Li-jun; Wang, Xiao-han; Guo, Jing-bo; Zhao, Li-dan; Fei, Yun-yun; Yang, Hua-xia; et al.
Abstract: The chromatin modifier enhancer of zeste homolog 2 (EZH2) methylates lysine 27 of histone H3 (H3K27) and regulates T cell differentiation. However, the potential role of EZH2 in the pathogenesis of rheumatoid arthritis (RA) remains elusive. We analyzed EZH2 expression in PBMC, CD4 + T cells, CD19 + B cell, and CD14 + monocytes from active treatment-naïve RA patients and healthy controls (HC). We also suppressed EZH2 expression using EZH2 inhibitor GSK126 and measured CD4 + T cell differentiation, proliferation and apoptosis. We further examined TGFβ-SMAD and RUNX1 signaling pathways in EZH2-suppressed CD4 + T cells. Finally, we explored the regulation mechanism of EZH2 by RA synovial fluid and fibroblast-like synoviocyte (FLS) by neutralizing key proinflammatory cytokines. EZH2 expression is lower in PBMC and CD4 + T cells from RA patients than those from HC. EZH2 inhibition suppressed regulatory T cells (Tregs) differentiation and FOXP3 transcription, and downregulated RUNX1 and upregulated SMAD7 expression in CD4 + T cells. RA synovial fluid and fibroblast-like synoviocytes suppressed EZH2 expression in CD4 + T cells, which was partially neutralized by anti -IL17 antibody. Taken together, EZH2 in CD4 + T cells from RA patients was attenuated, which suppressed FOXP3 transcription through downregulating RUNX1 and upregulating SMAD7 in CD4 + T cells, and ultimately suppressed Tregs differentiation. IL17 in RA synovial fluid might promote downregulation of EZH2 in CD4 + T cells. Defective EZH2 in CD4 + T cells might contribute to Treg deficiency in RA. Highlights: CD4 +  T cells from RA patients expressed lower EZH2, which suppressed regulatory T cells (Tregs) differentiation in vitro. EZH2 inhibition downregulated RUNX1 and upregulated SMAD7 expression, subsequently attenuating FOXP3 transcription. RA-derived synovial fluid and fibroblast-like synoviocytes suppressed EZH2 expression in CD4 + T cells.